Fibroblast growth factor-23 negates 1,25(OH)2D3-induced intestinal calcium transport by reducing the transcellular and paracellular calcium fluxes - Pissared Khuituan (2018)
The calciotropic hormone 1,25-dihydroxyvitamin D3[1,25(OH)2D3] has been known to stimulate intestinal calcium transport via both transcellular and paracellular pathways. Recently, we reported that the 1,25(OH)2D3-enhanced calcium transport in the mouse duodenum could be abolished by fibroblast growth factor (FGF)-23, but the targeted calcium transport pathway has been elusive. Herein, the 1,25(OH)2D3-enhanced calcium transport was markedly inhibited by FGF-23 and inhibitors of the basolateral calcium transporters, NCX1 and PMCA1b, suggesting the negative effect of FGF-23 on the transcellular calcium transport. Similar results could be observed in the intestinal epithelium-like Caco-2 monolayer. Although the Arrhenius plot indicated that FGF-23 decreased the potential barrier (e.g., activation energy) of the paracellular calcium movement, FGF-23 was found to modestly decrease the 1,25(OH)2D3-enhanced paracellular calcium transport and calcium permeability. Moreover, FGF-23 affected the 1,25(OH)2D3-induced change in duodenal water permeability as determined by tritiated water, but both 1,25(OH)2D3and FGF-23 were without effects on the transepithelial fluxes of paracellular markers,3H-mannitol and14C-polyethylene glycol. It could be concluded that FGF-23 diminished the 1,25(OH)2D3-enhanced calcium absorption through the transcellular and paracellular pathways. Our findings have thus corroborated the presence of a bone-kidney-intestinal axis of FGF-23/vitamin D system in the regulation of calcium homeostasis. © 2013 Elsevier Inc. All rights reserved.